2020
DOI: 10.3389/fonc.2020.01090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metabolic and Morphological Response Criteria for Early Prediction of Response and Survival in NSCLC Patients Treated With Anti-PD-1/PD-L1

Abstract: Introduction/Aim: Immunotherapy with immune checkpoint inhibitors (ICIs) has positively changed the history of several malignant tumors. In parallel, new challenges have emerged in the evaluation of treatment response as a result of their peculiar anticancer effect. In the current study, we aimed to compare different response criteria, both morphological and metabolic, for assessing response and outcome in patients with advanced non-small cell lung cancer (NSCLC) treated with ICI. Materials and Methods: Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Aiming to enlarge the study sample, data from further nine NSCLC patients treated with Nivolumab belonging to a different clinical trial for ICI (NCT03563482), meeting our inclusion criteria and showing radiological progression were considered. The details of the trial NCT03563482 are reported elsewhere [22,63,64].…”
Section: Study Populationmentioning
confidence: 99%
“…Aiming to enlarge the study sample, data from further nine NSCLC patients treated with Nivolumab belonging to a different clinical trial for ICI (NCT03563482), meeting our inclusion criteria and showing radiological progression were considered. The details of the trial NCT03563482 are reported elsewhere [22,63,64].…”
Section: Study Populationmentioning
confidence: 99%
“…Actually, not. Some reports have attempted to compare various methods, particularly in melanoma and NSCLC patients [ 14 , 38 , 39 , 40 , 41 , 42 , 43 ], proving the superiority of some of the utilized criteria over others ( Table 2 ). Ultimately, all available response criteria, metabolic or morphological, retain the capability to predict response and outcome.…”
Section: Response Assessment In Solid Tumors Treated With Checkpoint Inhibitorsmentioning
confidence: 99%
“…Castello et al 17 prospectively compared morphological and metabolic responses at 8 or 9 weeks after PD-1 blockade using 18 F-FDG PET/CT in 35 NSCLC patients. Although they assessed the metabolic response by the SUV value, 3 (75%) of 4 patients with PR had PMR or CMR, 14 (87%) of 16 patients with PD exhibited PMD, and SMD was observed in 4 (26%) of 15 patients with SD 17 . In patients with SD on CT, metabolic response by PET could discriminate those with longer survival 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Although they assessed the metabolic response by the SUV value, 3 (75%) of 4 patients with PR had PMR or CMR, 14 (87%) of 16 patients with PD exhibited PMD, and SMD was observed in 4 (26%) of 15 patients with SD 17 . In patients with SD on CT, metabolic response by PET could discriminate those with longer survival 17 . 18 F-FDG uptake based on PERCIST or immunotherapy-modified PERCIST accurately reflects the overall metabolic response and survival after PD-1 immunotherapy in NSCLC patients 4 , 14 , 18 .…”
Section: Discussionmentioning
confidence: 99%